(untitled) (Stato, Chiese e pluralismo confessionale, 2010)
A preliminary version of this paper was discussed at the European University Institute in Fiesole within the framework of the Religion and Politics working group chaired by Prof. Olivier Roy at the Department of Political Science. See Religion and Politics working group, European University Institute, Round table discussion about the ECtHR decision to ban crucifixes in Italian state schools, 26 November 2009, http://www.eui.eu/Personal/Researchers/Peace/rpwg.htm. SUMMARY: 1. PART I. Introduction – 2. National proceedings – 3. The case before the ECtHR – 4. The decision of the court – 5. The reaction to the decision – Part II. A BRIEF ANALYSIS OF THE JUDGMENT. - 6. The composition of the court – 7. The meaning of the crucifix – 8. The holding of the case: did the court reach the right decision? – 9. The concept of neutrality – 10. Conclusion.